PEMBUATAN SUSU SKIM KELAPA BUBUK MENGGUNAKAN ALAT PENGERING BEKU VAKUM - Purnamasari, Indah (Politeknik Negeri Sriwijaya, 2020)
Coconut Skim Milk Water is the main byproduct of coconut milk which is often overlooked. In fact, Coconut Skim Milk Water can be used as an alternative food ingredient that can meet calorie intake in the body with a protein content composition of 35% bk. Utilization of Coconut Skim Milk Water into Powdered Coconut Skim Milk was chosen to increase storage capacity and facilitate product application. One of the alternatives in drying coconut skim milk water is to use a Vacuum Freeze Dryer. This study aims to determine the effect of drying temperature and drying time on yield of powdered coconut skim milk and the effect of drying rate on temperature and drying time. The treatments that were varied in this study were variations in drying temperature (-25 C); (-20 ËšC); (-15 ËšC); (-10 C) and variations in drying time of 12 hours, 13 hours. The results of this study indicate that samples at primary temperature -25 ËšC, drying time 13 hours, vacuum pressure -70 cmHg and secondary temperature 50 ËšC are samples with optimum operating conditions.